Exploring form-finding techniques for funicular shells and domes - Rajasekaran, S. (Journal of Structural Engineering, 2024)
This paper examines the process of designing shell structures by selecting necessary forces to ensure the shell can bear applied loads primarily in axial compression with minimal bending. Instead of following conventional methods, the designer assumes a desired state of stress and determines the corresponding funicular shape using various boundary conditions. Two-dimensional structures result in funicular cables or arches, while three-dimensional structures are known as funicular shells, and domes derived from these shells are called funicular domes. Different numerical methods, such as Finite Difference, Finite Element Method, Boundary Integral Element, and Differential Quadrature Methods, can be used to obtain the funicular shape of a shell. This paper presents examples of cables, shells, and domes solved using these techniques and draws conclusions based on the results. The governing equation for shallow funicular shells and domes is Poisson’s equation, while a nonlinear partial differential equation is used for deep shells and domes. Overall, this paper provides insights into the application of various numerical methods in determining the shape of funicular structures.